Student Learning Motivation in Adaptive Physical Education through Small Game Activities - Ricky Almeda; H Heidari Nik; Mohamed Sifi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine and describe the level of students’ learning motivation in adaptive physical education through small-sided games among Outstanding Junior High School. Methodology: This study employed a descriptive quantitative method with a survey approach. Data were collected using questionnaires, observation, interviews, and documentation. The instrument was tested using Pearson Product Moment for validity and Cronbach’s Alpha for reliability. The sample consisted of 23 students selected through total sampling, and data were analyzed using percentage descriptive statistics. Main Findings: The results indicate that students’ learning motivation is in the high category, with intrinsic motivation being more dominant than extrinsic motivation. Students showed positive responses in physiological, safety, and self-actualization needs, as well as social interaction and appreciation. Small-sided games effectively promote active participation, enjoyment, and engagement in adaptive physical education learning. Novelty/Originality of this study: This study provides empirical quantitative data on learning motivation in adaptive physical education through small-sided games at the Outstanding Junior High School level, which is rarely explored. It integrates intrinsic and extrinsic motivational dimensions in a comprehensive framework, offering a holistic understanding of student motivation in special education contexts.